Adaptation of the Ego and Task Orientation in Sport Questionnaire (TEOSQ) in Argentine athletes - Alejandro Emilio Pagano; Nicolás Alejandro Vizioli (Interacciones)
Background: The theory of achievement goals in sport tries to explain the motivation of the individual from knowing what value and expectations he gives to the sporting activities he performs and the goals that he proposes, to define them or feel successful in them, starting from the assumption that sport is a context of achievement and that is why individuals will strive to demonstrate competence and ability. The Task and Ego Orientation in Sport Questionnaire is one of the most widely used measurement instruments to address this theory. However, there are no local studies that allow measuring the construct in adult Argentine athletes. For this reason, the objective of this study was to carry out the linguistic, conceptual, and metric adaptation of the TEOSQ in adult athletes from the Province of Buenos Aires. Methods: The study was instrumental, with an intentional non-probabilistic sampling, the adaptation of the instrument from English to Spanish was carried out, then an expert judgment, followed by confirmatory factor analysis to then investigate reliability coefficients and provide normative values. Results: The sample consisted of 258 Argentine athletes (63.36% women; 36.4% men) from the disciplines, basketball, volleyball, indoor soccer, field hockey, and soccer (Mean age = 24.41, SD = 6.55). The results obtained indicate an acceptable fit for the two-factor model evidenced in the literature, having discarded items 5 and 13 for presenting a low factor load (<.30). In turn, adequate internal consistency coefficients are provided (α =.77 and ω =.85 for ego orientation; and α =.82 and ω =.86 for task orientation), and normative values are provided. Conclusion: This study provides evidence of validity and reliability for the adapted version of the TEOSQ in Argentine athletes.